The Effect of Marital Adjustment on Prenatal Breast-Feeding Self- Efficacy in Pregnants - Yilmaz Findik, Fatma; Yagmur, Yurdagul (Journal of Midwifery, 2024)
This study was conducted to determine the effect of marital adjustment on prenatal breastfeeding self-efficacy in pregnant women.The sample of the descriptive study consisted of 319 pregnant women. Data were collected between January and March 2019. Personal Information Form, Marital Adjustment Scale (MARS), Prenatal Breastfeeding Self-Efficacy Scale (PESES) were used as data collection tools. Data were analysed using descriptive statistics, t test in independent groups, OneWay ANOVA, Kruskal Wallis, Mann Whitney U. It was found that 70.8% of the pregnant women were compatible in their marriages, and the age of the pregnant woman, her and her husband's educational status, income status, duration of marriage, pregnancy, birth and number of living children, and the effect of pregnancy on spousal relationship affected marital harmony (p